Modular Coordination and BIM: Development of Rule Based Smart Building Components. (2015) - Singh, Manav Mahan; Sawhney, Anil; Borrmann, André
Abstract: The introduction of computing tools to Architecture, Engineering & Construction (AEC) industry has enabled the professionals to navigate successfully from traditional design/drafting to Computer Aided Design/Drafting (CADD). Furthermore, the industry is slowly transitioning towards sophisticated Building Information Modelling (BIM), which necessitates the integration of domain specific knowledge into the BIM authoring tools. The approach presented in this paper elucidates the development of rule-based BIM objects which allows a designer to create building models within the rules of Modular Coordination (MC). With this development, a designer will be able to use MC standards to size and locate building objects in a modular reference frame. Integration of rules of MC with BIM authoring tool will enhance the design process and allow designers to automate some complex modelling/documentation activities requiring no design expertise. The development of rule-based BIM objects exploits the parametric modelling capabilities of BIM authoring tools in addition to visual programming tool to automate the modelling process. The research first explains development of rule based BIM objects which is extended to streamline the overall design process. The presented approach discusses the customization of BIM authoring tool for modelling a residential facility in MC using axial planning of structural elements. In the prototype system, the designer is guided by specific rules and constraints while providing sufficient options to develop variegated configuration. The integration of design rules of MC standards with BIM application will be influential to increase radical use of BIM for built environment especially in the prefabrication industry.